Acquired ankyloblepharon post purulent membranous conjunctivitis and its novel surgical management: A case report - Sharma, Nidhi; Nagar, Anjali (Nepalese Journal of Ophthalmology, 2022)
Introduction: Ankyloblepharon is a partial or complete fusion of eyelids by webs of skin. It may be congenital or acquired. Herein we report a rare case of acquired bilateral ankyloblepharon that developed after purulent membranous conjunctivitis. We will also discuss its unique surgical management which has not been reported previously in the literature. Case: A 21 year old male presented with complaints of narrowing of eyes for the last six months following an attack of acute purulent membranous conjunctivitis. Surgical excision of the adhesions was done. We used conjunctival autograft to cover the raw area left after excision as a new modality of treatment. The graft was successfully taken up and no recurrence of adhesions was found at 1 year follow up. Observations: Various modalities of treatment for ankyloblepharon have been reported which includes excision of tissue and suturing and amniotic graft. Here we have used conjunctival autograft on the raw area after excision of adhesions and the result obtained was good. Conclusion: To the best of our knowledge this is the first and a rare case of acquired ankyloblepharon in a young male following a single episode of purulent membranous conjunctivitis. Conjunctival autograft can be successfully used to cover the raw areas left after excision of adhesions.